Holding wild Snow crab, Chionoecetes opilio: effects of stocking density and feeding on survival and injury. (30th January 2016) - Siikavuopio, Sten Ivar; James, Philip; Olsen, Bjørn Ronald; Evensen, Tor; Mortensen, Atle; Olsen, Stein Harris
Abstract: In this study the effects of different stocking densities on survival, injury and weight of captive male snow crab were examined. The first experiment (I) was carried out in square plastic tanks (700 L) with stocking densities of 100 (L), 150 (M) and 200 kg m −3 (H) for 30 days. In a second experiment (II) snow crabs were kept at a stocking density of 50 kg m −3 and were either fed (F) or not fed (S) for the same period of 35 days. The last experiment (III), was carried out with stocking densities of 25 kg m −3 for 21 days with two groups, one with inactivated claw and one without rubber bands, with three replicates per treatment. In the first experiment mortality (H = 27, M = 26 and L = 36%) and occurrence of injuries (H = 27, M = 20 and L = 16%) were high in all groups. The weight loss during the experimental period was; H = 15.3, M = 10.9 and L = 15.5 g, and was not significant different between the groups. In experiment II the mortality (F = 13% and S = 14%) and injuries were lower (F = 12% and S = 17%). The average weight increased in the fed treatment and decreased in the starved treatments. In the last experiment there was no mortality in any of the groups and the levels of injury were low (5% and 7%). The results show that adult male snow crab cannot be stored at densities equal to or higher than 25 kg m −3 for 3 weeks without risk of mortality.